18.9k views
8 votes
A + 6.6 = 12.6 helpp please !

User TanjiroLL
by
5.0k points

2 Answers

7 votes

Answer:

it is 6

Explanation:

because if you subtract 12.6 - 6.6 = 6 so 6 + 6.6 is 12.6

User Shadowman
by
5.6k points
9 votes

Answer:

A = 6

Explanation:

To solve the equation A + 6.6 = 12.6, you need to isolate the variable "A," which represents an unknown value.

Subtract 6.6 from both sides of the equation:

=> A + 6.6 - 6.6 = 12.6 - 6.6

Simplifying this equation gives:

=> A = 6

Therefore, the solution to the equation A + 6.6 = 12.6 is A = 6.

User Suryanaga
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.